STRATEGI PEMASARAN ONLINE (STUDI KASUS FACEBOOK MARKETING WARUNK BAKSO MAS CINGKRANK DI MAKASSAR) - Ridho Azlam Ambo Asse (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Hasanuddin, 2018)
ABSTRACT This study aims to determine and analyze facebook marketing communication strategy used by Warunk Bakso Mas Cingkrank includes planning and implementation results to increasing sales in each branch. The methods used are observation, in-depth interviews and documentation. The research was carried out in Makassar with ten informants (business owners and founders, online marketing managers as well as personal Facebook admins, digital marketing as well as fanpage admins, social media content creators, consultants who also acted as social media marketing observers, as well as five selected consumers. purposive). Data were analyzed using Miles & Huberman model. The results show facebook accommodate existing components in marketing communication strategies such as providing consumer data to validate segmentation, targeting, and positioning as well as research materials in determining the production of facebook marketing content. Paid campaign advertisements facilities with specific detail targeting become the advantage of advertising using Facebook than conventional media, the amount of the advertising costs and the admin expertise as well as content creators are influence the distribution of publications and message interactions embedded in advertising campaigns. The marketing strategy was executed on Facebook fanpage, personal and group accounts. The three main components of facebook marketing are running the marketing mix such as advertising, sales promotion, personal selling, direct marketing, public relations and publicity. The popular marketing content on Facebook is soft selling methode and video. Facebook marketing as a new media tool in accordance with the key concept of new media including; collective intelligence, convergence, digital economy, interactivity, economic knowledge, Mobile Media, networking, participatory, user-generated content / user-guided innovation, Web 2.0. Keywords: facebook marketing, new media, online marketing communication strategy. ABSTRAK Penelitian ini bertujuan mengetahui dan menganalisis strategi komunikasi pemasaran facebook yang digunakan oleh Warunk Bakso Mas Cingkrank meliputi perencanaan dan hasil pelaksanaannya dalam meningkatkan penjualan di setiap cabang. Metode yang digunakan yaitu observasi, wawancara mendalam dan dokumentasi. Penelitian dilaksanakan di Makassar dengan informan sebanyak sepuluh orang (Pemilik dan pendiri usaha, Manajer online marketing sekaligus admin facebook personal, digital marketing sekaligus admin fanpage, pembuat konten sosial media, konsultan yang merangkap sebagai pengamat sosial media marketing, serta lima orang konsumen yang dipilih secara purposif). Data dianalisis dengan menggunakan model Miles & Huberman. Hasil penelitian menunjukkan facebook mengakomodasi komponen yang ada pada strategi komunikasi pemasaran seperti menyediakan data-data konsumen untuk memvalidasi segmentasi, targeting, dan positioning sekaligus menjadi bahan riset dalam menentukan produksi konten facebook marketing. Fasilitas Iklan kampanye berbayar dengan detail targeting yang spesifik menjadi keunggulan beriklan menggunakan facebook dibandingkan media konvensional, besar kecilnya biaya iklan serta keahlian admin juga pembuat konten berpengaruh pada sebaran publikasi pesan dan interaksi yang terjalin pada suatu kampanye iklan tersebut. Strategi marketing di eksekusi pada akun facebook fanpage, personal dan grup. Tiga komponen utama facebook marketing tersebut menjalankan bauran pemasaran seperti periklanan, promosi penjualan, penjualan secara pribadi, pemasaran langsung, hubungan masyarakat dan publisitas. Konten marketing populer pada facebook ialah dengan ciri cover/soft selling dan video. Pemasaran facebook sebagai piranti media baru sesuai dengan kunci konsep new media diantaranya; kecerdasan kolektif, konvergensi, ekonomi digital, interaktifitas, pengetahuan ekonomi, Mobile Media, jaringan, partisipatif, konten yang dibuat pengguna/inovasi yang dipandu pengguna, Web 2.0. Kata kunci: facebook marketing, new media, strategi komunikasi pemasaran online.